Prevalence of iron deficiency anaemia among postpartum mothers at Kallandiri PHC, Madurai - Nisha, Thankappan Subhadra; Govindasamy, Selvarani; Ravikumar, Jaynathi; Sheriff, Dhastagir Sultan (International Journal Of Community Medicine And Public Health, 2025)
Mothers are fostering the future citizens of our societies. Anaemia is the world’s second leading cause of disability and thus one of the most serious global public health problems. However, the problem of anaemia in postpartum is far more prevalent in the developing countries. Early diagnosis and identifying the possible risk factors are helpful to manage Post Partum Anaemia in time before further complications developed. A study is designed to find out the level of iron deficiency anaemia among Postpartum mothers in selected Primary Health Centre, Madurai and to find out the association between their selected demographic variables and baseline variables. A quantitative research approach and non- experimental (descriptive) research design were used to gather data from 100 Postpartum mothers using consecutive sampling technique. Self- structured questionnaires were used to collect information during interview and blood is collected for biochemical analysis of haemoglobin among Postpartum mothers. Data was analysed and interpreted and the results were derived. The study findings revealed that majority of the subjects 64 (64%) were having moderate anaemia, 26 (26%) were having mild anaemia 10 (10%) were having non anaemia and none of them having severe anaemia. There is statistically significant association between age (χ2=9.66, p=0.05), educational qualification (χ2=13.91, p=0.05), haemoglobin level at Antenatal period (χ2=14.35, p=0.01) and prevalence of iron deficiency anaemia among postnatal mothers at Kallandiri PHC, Madurai. Statistical significance was calculated using the Chi-square test. The study findings concluded that majority of Postpartum mothers are anaemic. Therefore, health awareness programmes can be conducted to create awareness among rural postnatal mothers regarding importance of iron rich diet and complications of anaemia.